Effect of Blended Learning with Micro-course on Mathematical Reasoning Ability of University Students - Wu, Si; Juithong, Suwana; Jirojphan, Wassaporn (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: With the rapid development of contemporary information technology, the online and offline blended learning model relies on information technology and mobile Internet to realize the organic combination of online and offline classroom teaching, creating a broader autonomous learning space for students. The purpose of this research is to evaluate the impact of blended learning with a micro course approach on students’ mathematical reasoning abilities and satisfaction. Methodology: This study sample selected were 30 freshmen students majoring in natural sciences at a university in Hainan which was derived from a single cluster random sampling method. The research tools are (1) Course lesson plan, (2) Mathematical reasoning ability test paper, and (3) Student satisfaction questionnaire. Conduct pre-test and post-test on the sample using mathematical reasoning ability test papers, and analyze the mean, standard deviation, and single sample t-test of the data using SPSS. Result: After using the blended learning micro course teaching method, students’ mathematical reasoning abilities were achieved by 77%, surpassing the predetermined criteria of 70%, and the difference is statistically significant at 0.05. Based on the scores from the statistical student satisfaction questionnaire, the overall results of the blended learning with micro course method by students are at a high level. Conclusion: The study confirms that blended learning with micro-courses significantly enhances mathematical reasoning abilities and meets the individual learning needs of students majoring in natural sciences.